Are soft skills conditioned by conflicting factors? A multiobjective programming approach to explore the trade-offs - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro; Henriques, Carla Oliveira (Science Direct, 2021)
Despite the relevance of noncognitive skills (i.e. soft skills) for individual development and for certain forms of employment, they tend to be overlooked in studies centred on educational performance. This study brings an additional contribution to the growing interest on these skills by exploring their main determinants and by providing an additional understanding of how they are influenced by socio-economic and family background. To this end, a multiobjective programming model has been developed, whose coefficients are instantiated by the results of several econometric estimations, in which distinct (and conflicting) aspects of multiple soft skills are considered. Hence, by coupling econometric with multiobjective optimisation modelling approaches we provide an overarching framework for assessing the trade-offs between the different dimensions of noncognitive skills. Data from the most populated region of Spain are used. Overall, our findings highlight the trade-off between different soft skills, which are particularly conditioned by students’ gender.
Keywords: Econometría; noncognitive skills; econometric analysis; multiple objective programming